Prognostic predictors of special technical and tactical training of Paralympic swimmers with lesions of the musculoskeletal system - Vinokurov, L. V.; Mosunov, D. F.; Nazarenko, Yu. A. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to identify and determine the predictors of special technical and tactical training of highly qualified Paralympic swimmers in the sport of persons with lesions of the musculoskeletal system (LMS).